Analysis Of Factors Affecting Interest In Saving In Sharia Banks: Study Of Literature And Perspectives Of Post-Baged Students In Sharia Economy - Simbolon, Linda Rosalina; Soemitra, Andri (International Journal of Cultural and Social Science, 2022)
Research on the factors that influence customer interest in saving in Islamic banks is inseparable from two factors, namely service and product quality. The development of Islamic Banks can be clearly observed that Banks operating by implementing systems based on sharia principles are able to answer the needs desired by customers. The development of Islamic banks itself does not escape the behavior of consumers who believe in the quality and quantity of products offered by banks. Behavior reflects the satisfaction received as a customer to the bank as a place to collect and manage their funds. Consumer behavior is a reflection of the behavior of customers in expressing the feelings received by the services they receive as customers.